2015
DOI: 10.5551/jat.28167
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic Acid Prevents Saturated Fatty Acid-Induced Vascular Endothelial Dysfunction: Involvement of Long-Chain Acyl-CoA Synthetase

Abstract: Aim: Vascular endothelial dysfunction is considered an early predictor of atherosclerosis. It has been proven that elevated blood levels of free fatty acids pose a substantial risk for the development of cardiovascular disease. In this study, we examined the effects of palmitic acid (PA), a saturated fatty acid, on endothelial function by using the expression of adhesion molecule, cytokines, and inflammatory protein as indicators, as well as investigated the effects of eicosapentaenoic acid, an n-3 polyunsatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…Taking into account the effects of FFA on inflammation, oxidative stress, and expression of adhesion molecules (5153), our results may support a role for FFA as a link between the (altered) gut microbiota, host metabolism, and disease status. It is interesting to note that differences among FFA in their ability to promote endothelial activation in vivo or in vitro have been demonstrated (5456), which is in line with the associations found in our study. Importantly, these biomarkers are considered as early preclinical indicators of CVD development in the long term (5760).…”
Section: Discussionsupporting
confidence: 92%
“…Taking into account the effects of FFA on inflammation, oxidative stress, and expression of adhesion molecules (5153), our results may support a role for FFA as a link between the (altered) gut microbiota, host metabolism, and disease status. It is interesting to note that differences among FFA in their ability to promote endothelial activation in vivo or in vitro have been demonstrated (5456), which is in line with the associations found in our study. Importantly, these biomarkers are considered as early preclinical indicators of CVD development in the long term (5760).…”
Section: Discussionsupporting
confidence: 92%
“…Our study revealed that EPA suppresses Wnt signaling in smooth muscle cells. EPA is also known to affect macrophages and endothelial cells [ 49 , 50 , 51 ]. Additionally, Wnt signaling is associated with inflammation and aging [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In human umbilical vein endothelial cells (HUVECs) that were exposed to ox-LDL, EPA improved the balance between NO and ONOO À1 , acting synergistically with statins [41]. EPA attenuated palmitic acideinduced generation of reactive oxygen species, expression of adhesion molecules and cytokines, activation of apoptosis-related proteins, and apoptosis in HUVECs [42,43]. EPA also inhibited lipid peroxidation in membrane vesicles with normal or elevated cholesterol levels; this effect was also augmented by the presence of a statin [44].…”
Section: Effects Of Epa On Endothelial Function/dysfunctionmentioning
confidence: 99%